Žemaičių Kalvarijos Kalnų maldyno istorija, muzika ir apeigos : tarpdisciplininė mokslo monografija History, music and rites of the Samogitian Calvary Hills prayer book - Motuzas, Alfonsas (Vytautas Magnus University, 2017)
Samogitian Calvary Hills is the Way of the Cross made of 20 sites, 19 stations in 19 chapels in the premises of Žemaičių Kalvarija town. "Samogitian Calvary Hills" is also the title used for a prayer book dedicated to walking the stations. This prayer book is used in Samogitia during the Good Friday and Saturday in churches and during funeral and commemoration of the deceased at home. "Hills" is a term used by Lithuanian Catholic Church clergy and editors of Samogitian folklore and religious books describing religious practice; it has derived from the title of the first edi¬tion prayer book published by Dominican monk Jurgis Kasakauskis in 1681. Afterwards "Hills" prayers and hymns were included in later prayer books. This continued until the declaration of the provisions of the Second Vatican Council (1962-1965). After the declaration of the provisions of the Second Vatican Council started printing a new versions of "Hills" prayers and hymns. This fact allowed noticing the problematic in change and expression of literal and musical texts of prayers and hymns in Hills prayer books. The problematic allowed formulating the research object - prayers, hymns, music and rites of "Hills" prayer books. Research goal - to analyse literary and musical texts of prayers and hymns in "Hills" prayer books and the origins of their music and rites, historiographic development and reasons for variations. The research validated the hypothesis that prayers, hymns and their mu¬sic in the "old" "Hills" prayer book are not created (except for intentions of stations and prayer "Let us pray" and hymns "Gracious Queen" ["Karalienė maloninga" - in Lithuania and "The most sacred Mother of Heavenly King" ["Dangaus Karaliaus Motina švenčiausia" - in Lithuania]) as it is stated, but composed and prepared prayer book on the initiative of Jesuit, Franciscan and Dominican monks based on calls, acclamations and hymns dedicated to the commemoration of the Passion of Jesus Christ in polish prayer books and hymnals during the time of counter reformation. It was newly edited and recreated by local priests and monks based on the documents of the Second Vatican Council (1962-1965).